Behavior of testosterone and cortisol during an intensity-controlled high-volume training period measured by a training task-specific test in men rowers - Rämson, R.; Jürimäe, J.; Jürimäe, T.; Mäestu, J. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study was to investigate changes in the stress hormones testosterone and cortisol after a task-specific exercise during a high-volume endurance training cycle in men rowers. Eight highly trained men rowers were investigated during a high-volume, low-intensity training period. A 2-hour, low-intensity, long-distance rowing (LDT) test was conducted at baseline, after a high-volume period, and after the recovery period. Training and performance intensities were obtained at the graded incremental test, were preset individually, and were the same during all LDTs. Fasting blood samples were taken during the same days as the LDTs. Exercise-induced blood samples were taken before, 5 minutes after, and 30 minutes after (post 30?) the completion of each LDT. There were no significant changes in fasting cortisol and testosterone values during the whole study period, and there were no significant changes in cortisol and testosterone concentrations during the LDT. However, testosterone concentration was significantly decreased at post 30? compared with posttest values during the second LDT that was held after the 2-week high-training-volume period, and, during the second LDT, post 30? values of cortisol tended to be decreased compared with posttest values (p = 0.063). In conclusion, changes in the concentrations of testosterone and cortisol after long-distance rowing indicate decreased adaptivity after the training-specific performance test.